The two Escherichia coli chromosome arms locate to separate cell halves. - Wang, X; Liu, X; Possoz, C; Sherratt, D (2006)
DNA replication divides the circular Escherichia coli chromosome into equal arms (replichores). Visualization of pairwise combinations of multiple genetic loci reveals that the two replichores occupy separate nucleoid halves, with the replication origin between; positions of loci on each replichore recapitulate the genetic map. Sequential replication-segregation regenerates the <left-right> structure by sequentially layering newly replicated replichore DNA to specific inner and outer edges of the developing sister nucleoids. Replication fork-dependent locus positions are imprinted, so that in most generations the <left-right> chromosome orientation in a mother cell is recreated as a <left-right-left-right> arrangement of sister chromosomes in daughter cells.</left-right-left-right></left-right></left-right>